Optimization Of Audio Visual Media To Improve Students' Concentration In Arabic Language Learning/ Optimalisasi Media Audio Visual Untuk Meningkatkan Konsentrasi Siswa Pada Pembelajaran Bahasa Arab - Hotimah, Khusnul; Noor, Fatwiah (Bumi Lingua Edu Center, 2024)
This study describes the optimization of audiovisual media to increase student concentration in Arabic language learning at MI Azharul Ulum 02 Malang. This study aims to describe the nature of audiovisual learning media and its varieties, the causes of decreased concentration in students, and the implementation of learning media using audiovisuals to overcome decreased concentration in students. This study uses a qualitative descriptive method of case study type. The data collection technique is observation and data techniques using observations at MI AZHARUL ULUM 02, totaling 35 students in 2024, and documentation. This article uses the Miles, M.B. and Huberman, A.M. model for data analysis. The study results showed that audiovisuals are divided into active and non-active. Audiovisual media to improve student concentration can train istima' and qiroah simultaneously, explain learning clearly, save time and costs, help educators deliver learning practically, and help students remember learning more. Two factors can affect student concentration: internal factors (assumptions, willingness or interest, and physical condition) and external factors (lack of support, environmental influences, and monotonous learning presentation models). As for the form of audiovisual implementation in Arabic language learning, researchers raised several material titles. Such as التّعارف, المهنة, اللّون, عدد, الأسرة. Audiovisuals are cartoon and animation videos that display educational videos and songs. After that, the educator guides learning by giving assignments to make videos, singing songs related to the material, and guiding children's understanding through brief explanations. Using audiovisual learning media to improve student concentration is effective for educators.